Teknik Ekstraksi dan Nanoenkapsulasi Komponen Bioaktif Buah Malaka: Tinjauan Literatur - Nida El Husna; Erliza Noor; Farah Fahma; Titi Candra Sunarti (AGROINTEK, 2022)
The bioactive components of malacca (Emblica officinalis), which consist of phenolic, alkaloids, phytosterols, organic acids, and vitamins, are valuable for human health. The yield and quality of the bioactive components in the extract highly depend on the extraction technique, so it is essential to know the development of research on extraction techniques of the bioactive components of malacca fruit. In addition, the bioactive components in the extract have limitations in their application due to their stability, solubility, absorption, and bioavailability properties. Currently, nanoencapsulation technology has been applied to extracts of bioactive components to improve their properties. This review aims to provide comprehensive information about extraction techniques to obtain bioactive components of malacca fruit and presents the technique and purpose of the nanoencapsulation of malacca fruit extract. In addition to conventional techniques, several modern extraction techniques such as microwave-assisted extraction (MAE), ultrasound (UAE), pulsed electric field (PEF), and supercritical fluid (SFE) have been used to extract bioactive components of malacca fruit. Modern extraction techniques can produce extracts of bioactive components with higher yields than conventional techniques. The application of nanoencapsulation technology to malacca fruit extract consists of nanoliposomes and nanoparticles can increase permeability, antioxidant activity, antidiabetic and anti-inflammatory properties of malacca fruit extract.